Multivariate approach in timber harvesting experiments in forest plantations - Guera, Ouorou Ganni Mariel; da Silva, José Antônio Aleixo; Ferreira, Rinaldo Luiz Caraciolo; Álvarez Lazo, Daniel Alberto; Barrero Medel, Héctor; Díaz Pita, Andrés Loreto (Instituto de Ecología, A.C., 2020)
This work was carried out with the objective of evaluating, technically and economically, timber extraction in plantations of Pinus caribaea var. caribaea of Macurije forest company located in the province of Pinar del Río, Cuba. For this, time and movement studies were carried out using "productivity" and "unit cost" of wood extraction as evaluation criteria. The skidders and oxen performance evaluation, in different harvest systems and slope classes, was performed through univariate and multivariate (cost and/or productivity) factorial experiments (3 × 3 × 2), following a randomized block design (B1 = 21 years and B2 = 32 years), with the factors "machinery" and "slope" with three and "harvest systems" with two levels. The feasibility and usefulness of the multivariate approach in the evaluation of timber extraction were evidenced; timber extraction is more viable with the tree length harvest systems in stands of 32 years. The interaction machinery-slope had a significant influence on the variation of the whole cost-productivity. The John Deere 548E skidder, for presenting lower unit cost and higher productivity than the J-80A, is recommended for semi-mechanized timber extraction. The most viable is the yoke of oxen because of its greater profitability. However, due to its low productivity, it can only be used in combination with other machines or during periods of decelerated production. Its exclusive use is impracticable since it would imply significantly increasing its quantity to compensate for its low productivity.